2016
DOI: 10.1111/aos.13283
|View full text |Cite
|
Sign up to set email alerts
|

Parinaud syndrome: a 25‐year (1991–2016) review of 40 consecutive adult cases

Abstract: Our series highlights the variable clinical presentation of Parinaud syndrome. The classic triad of conjugate upgaze paralysis, convergence-retraction nystagmus and light-near dissociation was only present in 65% of cases. Pineal neoplasms remain an important aetiological consideration; however, primary midbrain pathology including infarction and haemorrhage constituted the majority of our cases and should be considered in all patients. Conservative management approaches for ocular symptoms are sufficient in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
38
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 2 publications
7
38
2
Order By: Relevance
“…Also, Rojas et al reported a patient with minimal anomalies of PS showing slowed upward saccades and pupillary light‐near dissociation in the absence of upgaze palsy, convergence‐retraction nystagmus, and lid retraction . Additionally, the present patient had not only upward gaze palsy, but also ptosis, which could be observed in PS . As a consequence, we concluded that the phenomenology of the present case was highly compatible with PS.…”
mentioning
confidence: 48%
See 1 more Smart Citation
“…Also, Rojas et al reported a patient with minimal anomalies of PS showing slowed upward saccades and pupillary light‐near dissociation in the absence of upgaze palsy, convergence‐retraction nystagmus, and lid retraction . Additionally, the present patient had not only upward gaze palsy, but also ptosis, which could be observed in PS . As a consequence, we concluded that the phenomenology of the present case was highly compatible with PS.…”
mentioning
confidence: 48%
“…With regard to the first comment that pure upward gaze palsy without dorsal midbrain lesion makes the diagnosis of Parinaud’s syndrome (PS) doubtful, we disagree with this opinion. We believe that PS could be regarded as a clinical syndrome with a cluster of abnormalities of eye movement and pupil dysfunction, and the pathophysiology of PS is thought to be induced by dorsal midbrain dysfunction regardless of any specific lesion . We deduced that normal pressure hydrocephalus (NPH)‐induced compressive effect affecting the dorsal midbrain might result in upward gaze palsy and ptosis of the patient.…”
mentioning
confidence: 99%
“…Parinaud's syndrome or dorsal midbrain syndrome is characterized by conjugate vertical gaze palsy (especially upward) combined with variable degree of other ocular findings, including convergence‐retraction nystagmus, pupillary light‐near dissociation and eyelid retraction . Pretectal lesions affecting rostral interstitial medial longitudinal fasciculus, interstitial nucleus of Cajal or posterior commissure could result in such ocular abnormalities.…”
mentioning
confidence: 86%
“…Cardinal symptoms of idiopathic normal pressure hydrocephalus (iNPH) are a variable degree of parkinsonism including gait disturbance, cognitive impairment and urinary incontinence. However, upward gaze palsy, a characteristic feature of Parinaud's syndrome, has never been described as an early sign in patients with iNPH. We experienced a case of iNPH presenting with upward gaze palsy and mild parkinsonism including gait disturbance.…”
mentioning
confidence: 99%
“…However, as also referenced by the Authors, in a recent crucial review, it was found that the classical triad of PS was present in just 65% of cases . Nevertheless, PS can also be defined as supranuclear vertical gaze palsy, and dorsal midbrain lesion is a constant etiology of PS, as also found in the 40 consecutive adult patients in the same report by Shields et al Therefore, I believe that defining the clinical presentation of this patient as PS, based solely on upward gaze palsy and without supporting neuroimaging data, might not be rationale.…”
mentioning
confidence: 99%